SUPERVISI KLINIS DALAM PEMBELAJARAN DI LEMBAGA PENDIDIKAN - Nurlela Sabir; Bahrani; Akhmad Ramli (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
The evaluation and supervision system has a big impact on the implementation of learning, meaning that the learning strategy and its implementation are very dependent on the evaluation system in place and the supervision carried out. Therefore, this research will present the meaning of clinical supervision, goals of clinical supervision, characteristics of clinical supervision, and principles of clinical supervision. The method used is the literature study method through collecting books, previous research and articles. The results show that the application of clinical supervision in learning is very helpful in improving the quality of learning by providing direct guidance to educators or practitioners in the field. Clinical supervision focuses on monitoring, assessing and coaching to identify strengths and areas for improvement, with the aim of supporting professional development. Through this approach, educators can obtain constructive feedback, reflection on their practice, and more targeted support in overcoming challenges in the field. Overall, the application of clinical supervision can improve skills, knowledge and quality of teaching, as well as create a more effective learning environment for students